Modelling attributes of corporate tax evaders using resolved audit cases - Isa, Khadijah; Yussof, Salwa Hana; Zulkifli, Zukhaire; Mohdali, Raihana (2018)
Reducing tax evasion is vital mainly because an “enforced compliance” policy is costly and often very expensive (OECD, 2008). Many tax administrations put an enormous effort into combating tax evasion. Available evidence suggests that tax evasion has been found to be particularly acute in many developing countries, including Malaysia. In the effort to reduce overall tax evasion, fairly and cost-effectively target tax audits by the tax authority are essential. This can be achieved should key business characteristics of tax evaders are identified. As suggested by previous studies, six variables had been examined to see whether they are associated with effective tax rate (ETR) of tax evader companies. The variables analysed are size, leverage, return on asset, capital intensity, inventory intensity and receivables. The study is using archival data from the Inland Revenue Board of Malaysia (IRBM), consists of 3,010 tax audited cases resolved by the Corporate Tax Branch of IRBM in 2012. Out of this number, 903 companies that were imposed with penalties of 45% or more are considered as the tax evaders. Findings from this study may assist the tax authority in developing strategies to reduce tax evasion. Consequently, a fairly and cost-effectively target tax audits can be accomplished.